Determinants of suburban development controls: a Fischel expedition - McDonald, John F.; McMillen, Daniel P. (2004)
In addition to land-use zoning, development controls in the suburban municipalities of metropolitan Chicago include architectural reviews, appearance regulations, historical preservation areas, enterprise zones, tax-increment financing districts, development impact fees and regulations pertaining to group homes, mobile homes, factory-assembled homes and adult uses. Results of a factor analysis imply that development control policies tend to cluster into quality development regulations, regulations aimed at lower-class development and growth controls. Subsequent econometric analysis suggests that larger suburbs make greater use of nearly all types of development control. Suburbs with new housing and high median household incomes tend to have complex single-family zoning provisions. Suburbs with lower incomes, larger minority populations and greater poverty rates are more likely to use Enterprise Zones and TIF districts, have more complex zoning for apartment buildings and tend not to have development impact fees. - Reproduced.
Keywords: Local government